1997
DOI: 10.1042/cs0930519
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Nitric Oxide-Mediated Vasodilatation and Total Body Nitric Oxide Production in Healthy Old Age

Abstract: 1. Basal release of nitric oxide from the vascular endothelium maintains a constant vasodilating tone. Impaired nitric oxide-mediated vasodilatation has been described in hypertension and atheromatous disease. Circulatory diseases account for considerable morbidity and almost half of all deaths in people over the age of 75 years. 2. We have therefore compared nitric oxide-dependent vasorelaxation in 12 healthy elderly subjects with 12 young volunteers matched for blood pressure, cholesterol and glucose, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 19 publications
4
68
0
5
Order By: Relevance
“…FMD was not impaired by the test fats in our study, but was already quite low in our subjects: the fasting values were 2.6% of the resting diameter. This value is about half of that observed in our previous studies, but those studies were done in younger subjects, and FMD appears to decline with age (Lyons et al, 1997). Ong et al found a similar value for lean, young, healthy men (Ong et al, 1999), but most investigators reported higher values.…”
Section: Discussionsupporting
confidence: 45%
“…FMD was not impaired by the test fats in our study, but was already quite low in our subjects: the fasting values were 2.6% of the resting diameter. This value is about half of that observed in our previous studies, but those studies were done in younger subjects, and FMD appears to decline with age (Lyons et al, 1997). Ong et al found a similar value for lean, young, healthy men (Ong et al, 1999), but most investigators reported higher values.…”
Section: Discussionsupporting
confidence: 45%
“…The stiffening of the vasculature and its diminished responsiveness to NO associated with increasing age 47 may have attenuated the effect of dietary nitrate supplementation on both the macrovascular and microvascular measures examined herein. This diminished vascular responsiveness to NO may be an important limiting factor to inorganic nitrate-based therapeutic strategies in older age groups.…”
Section: Discussionmentioning
confidence: 94%
“…There is also significant evidence to suggest that NO deficiency develops during normal aging. Endothelial NO-dependent vasodilation is impaired with advancing age in normal man and rats (Lyons et al, 1997;Cernadas et al, 1998;Bode-Boger et al, 2003). Total body NO production can be estimated from the urinary excretion of NO x (NO x = NO 2 + NO 3 ; the stable oxidation products of NO), providing that the NO x intake is controlled.…”
Section: Nitric Oxidementioning
confidence: 99%